2016
DOI: 10.1071/en15237
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation products of α- and β-amyrins: potential tracers of abiotic degradation of vascular-plant organic matter in aquatic environments

Abstract: Environmental contextHow can we know what happens to organic matter in aquatic environments? Although several compounds exist that can be used to trace the origin and state of organic matter, not many are sufficiently stable and specific to trace degradation processes, but α- and β-amyrins can fulfil that role. Such knowledge will help us better understand and better quantify carbon fluxes in riverine and marine environments. AbstractIn order to fulfil the current need for stable and specific tracers to monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 33 publications
0
19
2
Order By: Relevance
“…Also, because of the set of lipid tracers used, it is clear that the autoxidative processes observed acted on SPM of terrestrial origin [9,10]. It has been demonstrated that autoxidation is induced when particulate matter is incubated in seawater, and this was explained by the potential desorption of metallic ions upon contact with seawater [6].…”
Section: Rhone River Spm Incubationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, because of the set of lipid tracers used, it is clear that the autoxidative processes observed acted on SPM of terrestrial origin [9,10]. It has been demonstrated that autoxidation is induced when particulate matter is incubated in seawater, and this was explained by the potential desorption of metallic ions upon contact with seawater [6].…”
Section: Rhone River Spm Incubationsmentioning
confidence: 99%
“…Betulin and both amyrins are also unambiguous tracers of terrestrial vascular plants [9,10]. It has been long known that transition metals can catalyze autoxidation in biological systems [7,8], but could there be other drivers in the environmental systems?…”
Section: Tracers Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…These ubiquitous compounds are typically employed as general tracers of higher plant input during environmental studies. Recently, it was demonstrated that autoxidation (free radical oxidation) of α‐ and β‐amyrins affords 11α‐hydroperoxy‐urs‐12‐en‐3β‐ol ( 5 ) and 11α‐hydroperoxyolean‐12‐en‐3β‐ol ( 6 ), respectively (Scheme ). Compounds 5 and 6 , which are not affected by NaBH 4 reduction which is often employed during the treatment of natural samples containing labile hydroperoxides, are thermally cleaved to the corresponding ketones (3β‐hydroxy‐urs‐12‐en‐11‐one ( 7 ) and 3β‐hydroxy‐olean‐12‐en‐11‐one ( 8 )) during gas chromatography (GC) or GC/mass spectrometry (MS) analyses using hot injectors (splitless) (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…The ketones 7 and 8 were thus proposed as tracers of abiotic degradation (autoxidation) of terrestrial higher plants in the marine realm . Although very high proportions of these tracers could be easily detected by GC/MS operating in selected ion monitoring (SIM) mode in particulate matter and sediment samples collected in the Arctic and tropical zones, their quantification in samples where terrestrial organic matter is present in lesser proportions remains more problematic.…”
Section: Introductionmentioning
confidence: 99%